The influence of maturation and sex on pelvis and hip kinematics in youth distance runners. Issue 3 (March 2022) - Taylor-Haas, Jeffery A.; Long, Jason T.; Garcia, Micah C.; Rauh, Mitchell J.; Paterno, Mark V.; Brindle, Richard A.; Bazett-Jones, David M.; Ford, Kevin R.
Abstract: Objectives: This study aimed to investigate differences in stance phase pelvic and hip running kinematics based on maturation and sex among healthy youth distance runners. Design: Cross-Sectional. Methods: 133 uninjured youth distance runners (M = 60, F = 73; age = 13.5 ± 2.7 years) underwent a three-dimensional running analysis on a treadmill at a self-selected speed (2.8 ± 0.6 m·s −1 ). Participants were stratified as pre-pubertal, mid-pubertal, or post-pubertal according to the modified Pubertal Maturational Observation Scale. Stance phase pelvis and hip range of motion (RoM) and peak joint positions were extracted. Two-way ANCOVAs (sex, maturation; covariate of running velocity) were used with Bonferroni-Holm method to control for multiple comparisons with a target alpha level of 0.05. Results: A two-way interaction between sex and maturation was detected ( p  = 0.009) for frontal plane pelvic obliquity RoM. Post-hoc analysis identified a maturation main effect only among females (p˂0.008). Pelvic obliquity RoM was significantly greater among post-pubertal ( p  = 0.001) compared to pre-pubertal females. Significant main effects of sex ( p  = 0.02), and maturation ( p  = 0.01) were found for hip adduction RoM. Post-hoc analysis indicated a significant increase in hip adduction RoM from pre-pubertal to post-pubertal female runners ( p  = 0.001). A significant main effect of sex was found for peak hip adduction angle ( p  = 0.001) with female runners exhibiting greater maximum peak hip adduction compared to males. Conclusions: Maturation influences pelvic and hip kinematics greater in female than male runners. Sex differences became more pronounced during later stages of puberty. These differences may correspond to an increased risk for running-related injuries in female runners compared to male runners.